2016
DOI: 10.15408/kordinat.v15i1.6311
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesalahan Gramatikal Teks Terjemah (Indonesia-Arab) Dalam Pendidikan Bahasa Arab

Abstract: Analisis Kesalahan Gratikal Teks Terjemah (Indonesia-Arab) dalam Pendidikan Bahasa Arab. Penelitian ini dimaksudkan untuk memperoleh pemahaman yang mendalam mengenai kesalahan gramatikal dalam teks hasil terjemah. Sebagai sumber data dalam penelitian ini adalah teks hasil terjemah. Fokus dari penelitian ini adalah kesalahan morflogis dan sintaksis bahasa arab setelah diterjemahkan dari Bahasa Indonesia. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan analisis isi. Instrumen peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…"Found errors include word and verb state morphology, and errors in the syntax of phrases, clauses, sentences, and preposition errors. The error occurred due to the influence of Indonesian language into Arabic" (Fahmi, 2015). Similar research has also been conducted by the author (2013), namely examining the regularity and irregularity of sentence arrangement in the thesis of students who got and did not get Indonesian Language courses at the Faculty of Economics, University of Semarang and Faculty of Animal Husbandry, Diponegoro University.…”
Section: Introductionmentioning
confidence: 60%
“…"Found errors include word and verb state morphology, and errors in the syntax of phrases, clauses, sentences, and preposition errors. The error occurred due to the influence of Indonesian language into Arabic" (Fahmi, 2015). Similar research has also been conducted by the author (2013), namely examining the regularity and irregularity of sentence arrangement in the thesis of students who got and did not get Indonesian Language courses at the Faculty of Economics, University of Semarang and Faculty of Animal Husbandry, Diponegoro University.…”
Section: Introductionmentioning
confidence: 60%
“…In teaching Nahwu grammar, for example, it must begin with material about perfect sentences, but the details of the presentation material must be taught about isim, Based on the results in Figure 2, it can be seen that students more often practice direct sentences or practice directly translating sentences to learn Arabic grammar as many as 50% of respondents. As from various studies, it is shown that the qowaid and tarjamah methods are widely used by teachers in learning grammar and show that the use this method is very effective in improving students' grammatical abilities (Fahmi, 2016;Kasanah & Sauri, 2020;Rodliyah Zaenuddin, 2012). As many as 31.18% of other students study grammar by reading nahwu shorof books such as Jurumiyyah, nahwu wadhih etc.…”
Section: Grammatical Element Language Acquisition Strategymentioning
confidence: 99%
“…Basically, research on semantic-grammatical error analysis of text translation has been previously done. Fahmi (2016) shows that the mistakes made by students include: word and verb morphology as well as syntactic errors at the level of phrases, clauses, sentences, and letter errors at the level of prepositions. This error occurred because of the influence of Indonesian into Arabic.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, errors are caused by native language disorders, misuse of sentence fragments, overuse, lack of grammatical knowledge, errors in sentence formation. Furthermore, Fahmi (2016) emphasized his findings that students' mistakes included word and verb morphology as well as syntactic errors at the level of phrases, clauses, sentences, and letter errors at the level of prepositions. This error occurred because of the influence of Indonesian on Arabic.…”
mentioning
confidence: 99%